DECODING OF NON-TRAUMATIC ABDOMINAL PAIN: MULTIDETECTOR COMPUTED TOMOGRAPHY SCAN VERSUS ULTRASOUND: A RETROSPECTIVE CROSS-SECTIONAL STUDY - SANTOSH KUMAR PANDA; MADHURI PANIGRAHI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Abdominal pain is one of the common presentations in outpatient and causality of hospitals. Ultrasound (USG) and computed tomography (CT) scans are commonly used to assess the cause of abdominal pain. The primary objective was to determine which modality (CT scan/USG) to prefer for evaluation of abdominal pain. The secondary objective was to determine whether to consider for USG scan, even if a multi-detector CT (MDCT) has already been done. Furthermore, we wanted to estimate various causes of abdominal pain. Methods: All patients with any duration and any kind of abdominal pain were included in the study. A total of 200 cases were taken for analysis. All CT scans in this study were performed using a 128-slice MDCT scanner. USG report findings and CT scan findings were compared. Final diagnosis at the time of discharge from the hospital was noted for each case. Both CT scan and USG report findings were compared with the final diagnosis at the time of discharge from the hospital. Following variables were analyzed: – (1) Age distribution, (2) gender distribution, (3) patients found CT positive, (4) patients found USG positive, (5) correlation between CT positive and USG positive, (6) whether main cause of pain detected by CT scan, and (7) whether main cause of pain detected by USG study. Results: Out of the 200 patients, 53% were males and 47% were females. The mean age was 44.42 years. The most common age group was the 5th decade. There was a nearly equal percentage of detection of principal etiology of pain by CT and USG among male and female patients. USG was more diagnostic in the 5th decade and later age groups compared to the younger age groups. A CT scan was diagnostic in almost all age groups except the 2nd decade. Pancreatitis (19%) and cholecystitis (15.5%) were the most common causes of abdominal pain. CT scan showed positive findings in 88.5% of cases, whereas USG showed positive findings in 76.5% of cases. In 85% of cases, there was either partial or full correlation of findings between CT and USG. In 15% cases, no correlation of findings was seen. In 84% of cases, the principal etiology of pain was detected by CT scan. In 61.5% cases, USG could detect the principal cause of pain. In 75% of cases where USG showed positive findings, the CT scan also showed positive findings. Again, in 10% of cases where USG was negative, CT was also negative. Furthermore, 13.5% of USG negative cases were positive in CT, and 1.5% of CT negative cases were USG positive. Out of 177 patients having positive findings in CT, 94.91% patients were true positives. Out of 153 patients having positive findings in CT, 80.39% patients were true positives. In 26% of cases, where USG was not able to detect the cause of pain, CT could detect it. In comparison, only in 3.5% of cases where CT was not able to detect the cause of pain, USG could detect it. Conclusion: CT scan is more sensitive and specific for abdominal pain evaluation . If a CT scan has already been done, and satisfactory information related to the clinical diagnosis is found in the CT scan, then it is less likely to get additional information in a USG done subsequently.